Artificial Intelligence and Healthcare in Emerging Markets - Mrazek, Monique; O'Neill, Felicity (International Finance Corporation, Washington, DC, 2020)
Half of the world’s population remains without access to essential health services, with many individuals driven into poverty each year by out-of-pocket health expenses. UNCTAD estimates that to meet health-related Sustainable Development Goal objectives, over 140 billion dollars in private sector finance is required annually between 2015 and 2030. Significant investments in health technology, including those using digital health and artificial intelligence, are expected to contribute to bridging the health service gap in emerging markets, given the potential of these new innovations to reach underserved patients. Many health-tech innovators are integrating AI into their product solutions, with early examples showing promise in improving diagnoses, reducing costs, and enabling access to remote health services. COVID-19 has accelerated the pace of transition to digital health applications, including those that integrate AI. On a system-wide level, much remains to be done by all healthcare stakeholders to create sustainable ecosystems that facilitate these innovations in achieving scale while beneficially reaching the lowest-income patients in emerging markets.